Spatiotemporal clustering of suicide attempt in Kermanshah, West-Iran - Zangeneh, Alireza; Khademi, Nahid; Farahmandmoghadam, Naser; Ziapour, Arash; Naderlou, Reyhane; Oghli, Somayyeh Shalchi; Teimouri, Raziyeh; Yenneti, Komali; Moghadam, Shahrzad (Frontiers in Psychiatry, 2023)
Background: A suicide attempt is a major societal problem because it imposes high costs on societies worldwide. This paper analyses the spatiotemporal clustering of suicide attempt in Kermanshah, Iran from 2006-14. Methods: This study draws on 18,333 individuals (7234 males and 11097 females) who attempted suicide across the Kermanshah province. Data was collected from the records of individuals registered in hospitals across the Kermanshah province between 2006 and 2014. Mean Center, Standard Deviational Ellipse (SDE), Moran's I and Kernel Density Estimation (KDE) in Arc/GIS10.6 software were used for the analysis of the spatial distribution of suicide attempt, while the chi-squared test in SPSS was used to examine the different demographic variables between groups within/outside spatial clusters of suicide.The results show that a total of 18,331 suicide attempts (39.46% male and 60.53% female) were reported between 2006 and 2014 in the Kermanshah province. The spatial pattern of suicide attempts was clustered in 16 clusters (6 high clusters and 10 low clusters) and statistically significant differences were found within and outside the hotspots of suicide attempts. Most hot spots were formed in and around cities. Younger people were at a greater risk. The rate of suicide attempts reduced in illiterate people and increased in people with university degrees. Unmarried people were associated with a higher risk of suicide attempt than was married status for both males and females.The results of this study could help public health practitioners and policymakers in Iran prioritize resources and target efforts for suicide attempt prevention.